A giant mediastinal liposarcoma weighing 3500 g resected with clam shell approach, a case report with review of literature. (2017) - Sugiura, Yasoo; Hashizume, Toshinori; Fujimoto, Hiroyuki; Nemoto, Etsuo
Highlights: Mediastinal liposarcoma weighing 3500 g could be resected using calm shell approach. The present study analyzed 61 surgical cases of mediastinal liposarcoma. Adjuvant therapy did not significantly suppress the recurrence. Complete resection is the only means to achieve the favorable outcome. Abstract: Introduction: Liposarcoma is rare in the mediastinum and is less than 1% of all mediastinal tumors. In the present report, we demonstrated our case and summarized the principal treatment of the mediastinal liposarcoma with literature review. Presentation of case: A 50-year-old man presented at our hospital with complain of dyspnea. Chest radiography showed remarkable cardiomegaly. Computed tomography revealed an anterior mediastinal tumor from the level of the cephalic vein to the diaphragm of bilateral thoracic cavity with fat component. Using clam shell approach, complete en bloc resection of the tumor was performed. The weight of the tumor was 3500 g. The pathological findings were 0that size of adipocyte and lipoblast were different, and the nuclei of atypical stromal cell were misshapen. Immune-histologic examination was negative for MDM2 and cyclin-dependent kinase 4. The diagnosis was liposarcoma, well-differentiated type. He could discharge 10 days after surgery. Without adjuvant therapy, disease free survival for three years has passed. Discussion: From 1990–2016 in Japan, 60 cases of the mediastinal liposarcoma were reported. In analysis of the 61 cases including the present case, adjuvant therapy was performed in 14 cases, subsequently, and recurrence was recognized in 5 cases. Adjuvant therapy did not significantly suppress the recurrence. Conclusion: Mediastinal liposarcoma weighing 3500 g could be resected using calm shell approach, and no recurrence interval for 3 years has been achieved without adjuvant therapy. Complete resection is the only means to achieve the favorable outcome in mediastinal liposarcoma.